Pelaksanaan Sistem Pemodelan Maklumat Bangunan (BIM) Bagi Mengurangkan Kos Dalam Pengurusan Fasiliti - Mohd Fadzil, Anissa Imanina; Yahya, Mohd Yamani (Research in Management of Technology and Business, 2021)
Facility Management (FM) spans multiple disciplines to ensure the functioning of the built environment by integrating people, places, processes, and technology. Yet there are some problems that arise in FM especially in terms of costs incurred losses because of operating and maintenance costs. The cost of operation and maintenance has 4-5 times greater than the cost of construction. Therefore, implementing the Building Information Modeling (BIM) system is said to increase the efficiency of Facility Management and be able to solve the cost problem. However, the use of BIM in FM is still not widely used. Thus, the objective of this study is to examine the importance of implementing BIM system to reduce the cost of Facility Management (FM). In addition, this study was also conducted to identify the challenges of BIM implementation in Facilities Management to reduce its management costs. The study adapted the qualitative method by interviewing three (3) representatives of FM companies in Selangor involved in using BIM-FM. All interview data were analyzed using Content Analysis method. Findings show that the use of BIM can help reduce costs in FM management through 3D model visualization and model data and information developed. Moreover, the main challenges of BIM implementation in FM are its management cost is high technology cost, data used is large, lack of knowledge about the importance of BIM in FM, management change, and high tool cost. It is hoped that this study can identify the real importance of BIM in reducing the cost of FM and can identify the challenges that need to be overcome by the facility management to use BIM to reduce its management costs.